Utilizacion de octreotide en el Hospital Nacional Edgardo Rebagliati Martins-- EsSalud en el año 2007” - Altamirano Castillo, Leslie Carol (2008)
The present study is descriptive, traverse and retrospective type, whose purpose was focused in determining the utilization of Octreotide at different services of Edgardo Rebagliati Martins Hospital in 2007, in order to evaluate the consumption tendency, also possible deviations in the course of the year that surpose an irrational use of this medication. The consumption of Octreotide was expressed in DDD/100 bed – day, using the methodology recommended by the world organization of the health for the methodology of the studies about use of medications. The data were obtained of the on-line system of the department of pharmacist and statistic of the hospital. The total consumption of Octreotide was of 0.5489 DDD/100 bed - day. The service that presented a bigger consumption was the gastroenterology and it reached its higher pick in July. The meanly diagnostic associate to use of Octreotide in the Edgardo Rebagliati Martins Hospital was Hemorrhagic Digestive. The consumption of Octreotide in 2007 presented a curve of variable tendency with a positive correlation coefficient, not statistically significant